Computerized intrapartum electronic fetal monitoring: analysis of the decision to deliver for fetal distress. - Georgieva, A; Payne, S; Moulden, M; Redman, C (2011)
We applied computerized methods to assess the Electronic Fetal Monitoring (EFM) in labor. We analyzed retrospectively the last hour of EFM for 1,370 babies, delivered by emergency Cesarean sections before the onset of pushing (data collected at the John Radcliffe Hospital, Oxford, UK). There were two cohorts according to the reason for intervention: (a) fetal distress, n(1) = 524 and (b) failure to progress and/or malpresentation, n(2) = 846. The cohorts were compared in terms of classical EFM features (baseline, decelerations, variability and accelerations), computed by a dedicated Oxford system for automated analysis--OxSys. In addition, OxSys was employed to simulate current clinical guidelines for the classification of fetal monitoring, i.e. providing in real time a three-tier grading system of the EFM (normal, indeterminate, or abnormal). The computerized features and the simulated guidelines corresponded well to the clinical management and to the actual labor outcome (measured by umbilical arterial pH).